Influence of Promotional Strategies, Brand Image, Quality of Service and Price Against Community Trust: Study on TK II Hospital dr. Soepraoen - Jamzuri Jamzuri (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Community trust in a health institution is fundamental. Trust is a number of specific beliefs about integrity (trustworthy party honesty and ability to keep promises), behevolence (trustworthy attention and motivation to act in accordance with interests that trust them), competency (the ability of trusted parties to carry out trusting needs) and predictability (consistency in the behavior of trusted parties). The purpose of this study is to influence the promotion strategies, brand image, service quality, and price on public trust (Studies in Soepraoen Hospital Malang). The research design used is quantitative research. The research method used is quantitative research method causal research. The sampling technique used proportional sampling with a sample of 100 respondents. Data analysis techniques using multiple linear regression tests. The results showed that the descriptive results of promotion strategy variables showed an overall average value of 4.15 with a percentage of 26% and a good category, descriptive Brand Image variables had an overall average value of 4.05 with a percentage of 41% with good categories, in the descriptive variable Price Performance had a value the overall average of 4.10 in the good category with a percentage of 30%, in the Service Quality variable has a mean overall score of 4.07 in the good category of 36%, and the variable patient trust during treatment has an overall average value of 3.99 in the good category with percentage 68%. Of the 100 respondents studied in the promotion strategy have a significant influence on trust, in brand image has a significant influence on trust, at prices having a significant influence on trust, on service quality has a significant influence on trust, and simultaneously for each each promotion strategy variable, brand image, price, and service quality have a significant influence on trust. The trust variable is more influenced by the service quality variable than the promotion strategy, brand image, and price variable.